A mixture theory of electromagnetism and superconductivity - Eringen, A.Cemal (International journal of engineering science, 1998)
A continuum theory is introduced for mixture of fluids and elastics solids interacting with electromagnetic (E-M) fields and superconductors. Mechanical and E-M balance laws are given for mixtures consisting of N-species. Thermodynamically admissible constitutive equations are obtained for binary mixtures of heat conducting elastic solids and viscous fluids. Species may be regular conductors and/or superconductors. Mixtures of two viscous fluids, a fluid and an elastic solid and two elastic solids are considered. Field equations are given for both the mixtures whose species are subject to distinct E-M fields or to the same E-M fields.